2019
DOI: 10.1073/pnas.1900278116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evidence for tracking the seasonality of photosynthesis with solar-induced fluorescence

Abstract: Northern hemisphere evergreen forests assimilate a significant fraction of global atmospheric CO2 but monitoring large-scale changes in gross primary production (GPP) in these systems is challenging. Recent advances in remote sensing allow the detection of solar-induced chlorophyll fluorescence (SIF) emission from vegetation, which has been empirically linked to GPP at large spatial scales. This is particularly important in evergreen forests, where traditional remote-sensing techniques and terrestrial biospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
270
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 274 publications
(321 citation statements)
references
References 70 publications
15
270
0
3
Order By: Relevance
“…The contributions of PAR in , fPAR, LUE, and F 760,y to the variations in GPP and F 760 might differ at early growth stages as well as at the seasonal scale across the whole growing season. In addition, the rapid change of canopy structure and physiology of crop ecosystems differs from many natural ecosystems like forests or grasslands (Magney et al, ). Further studies are required to test whether the findings and the framework in this study are applicable or not to a different period of the growing season for maize or to other ecosystems with different characteristics of canopy structure and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of PAR in , fPAR, LUE, and F 760,y to the variations in GPP and F 760 might differ at early growth stages as well as at the seasonal scale across the whole growing season. In addition, the rapid change of canopy structure and physiology of crop ecosystems differs from many natural ecosystems like forests or grasslands (Magney et al, ). Further studies are required to test whether the findings and the framework in this study are applicable or not to a different period of the growing season for maize or to other ecosystems with different characteristics of canopy structure and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…SIF has been shown to be a robust proxy for GPP (Frankenberg & Berry, ; van der Tol et al, ). While nonlinear relationships between GPP and SIF have been observed at leaf and flux‐tower scales under certain conditions, for example, strong incoming light (Magney et al, ; Verma et al, ), linear relationships have been generally observed at ecosystem and regional scales (Frankenberg et al, ; Li et al, ; Magney et al, ; Sun et al, ). The robust linear relationship at increasing scales is likely because satellite measurements are primarily measuring an integrated canopy average of low Photosynthetically Active Radiation (PAR).…”
Section: Methodsmentioning
confidence: 99%
“…Because SIF is a measurement of re‐emitted light, it is less prone to signal saturation in dense canopies (Frankenberg & Berry, ), and thus has the potential to provide improved coverage of tropical forest ecosystems. More recent satellite efforts to measure SIF, including NASA OCO‐2 and ESA TROPOMI, show high fidelity compared to ground observations (Köhler et al ., ; Magney et al ., ), providing increased confidence in the use of satellite SIF to accurately measure the timing and magnitude of GPP across diverse global ecosystems. The potential for satellite SIF observations as a constraint on CFE depends on continued development of merged, long‐term SIF records with well‐characterized estimates of uncertainty (Sun et al ., ; Schimel et al ., ); and improved logic for direct incorporation of SIF observations into models (Lee et al ., ; MacBean et al ., ; Norton et al ., ; Gu et al ., ; Schimel et al ., ).…”
Section: Satellite Observations Can Constrain Direct and Indirect Effmentioning
confidence: 99%
“…Long-term satellite SIF observations are a direct measure of the light re-emitted from Chl during the light reactions of photosynthesis, and theory and observations show that SIF is correlated with photosynthetic activity in a dynamic fashion that is directly linked to APAR and LUE (Porcar-Castell et al, 2014;Yang et al, 2015;Smith et al, 2018;Magney et al, 2019) (Figs 2, 3). Thus, together satellite fAPAR and SIF estimates capture changes in photosynthesis per unit light absorbed (i.e.…”
Section: Lue Constraintsmentioning
confidence: 99%